2021
DOI: 10.1111/cch.12896
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated mothers' views of their children's experience: A qualitative study in French nurseries

Abstract: Context In France, young children of incarcerated women live with their mothers in prison in specific units called nurseries, up to the age of 18 months. Only a few studies have examined the impact of this environment on these children. This study sought to explore through mothers' narratives how they perceive their children to experience this environment and how it affects their development. Method We used semistructured interviews to collect the perceptions of 25 mothers about their children's experience of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…2 ). Three specific theories were most commonly referenced: attachment theory, 25 , 28 , 29 , 30 , 33 , 38 , 41 , 42 , 43 , 46 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 fundamental human rights and the best interest principle, 26 , 27 , 30 , 31 , 32 , 35 , 40 , 46 , 47 , 48 , 51 , 56 , 57 , 58 , 60 , 61 and gender responsive strategies. 25 , 46 , 55 , 57 , 59
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ). Three specific theories were most commonly referenced: attachment theory, 25 , 28 , 29 , 30 , 33 , 38 , 41 , 42 , 43 , 46 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 fundamental human rights and the best interest principle, 26 , 27 , 30 , 31 , 32 , 35 , 40 , 46 , 47 , 48 , 51 , 56 , 57 , 58 , 60 , 61 and gender responsive strategies. 25 , 46 , 55 , 57 , 59
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 publications referencing attachment theory, 20 suggested that M&Cs were beneficial to both incarcerated mothers and their children, while only one publication 30 presented the counter-argument that a prison environment is not suitable for healthy parent-child attachment or bonding. The reported benefits of M&Cs in terms of attachment theory can be grouped into 3 categories: M&Cs enable sustained contact between mothers and their offspring and enhance the mother–infant or mother–child bond 25 , 28 , 29 , 33 , 38 , 42 , 48 , 52 , 54 , 55 , 56 , 58 , 59 , 60 , 61 Children involved in M&Cs have improved early social, psychological, and emotional development and later life outcomes 25 , 28 , 29 , 33 , 38 , 43 , 46 , 49 , 52 , 53 , 54 , 56 , 57 , 58 , 59 M&Cs provide mothers with a motivation to be rehabilitated and to shift away from criminal behaviour 25 , 29 , 38 , 55 , 60 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, considering adults' perspectives both during and after incarceration offers views on children's adjustment across time and space. Other studies that have examined parent perspectives on the impact of incarceration for children (e.g., Correa et al, 2021; Ogrizek et al, 2021) often focused on the prerelease period alone. This creates the potential of a false dichotomy between “before” and “after” incarceration periods.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have explored the physical impact of imprisonment while pregnant, fewer have focused on these mothers' psychological outcomes and experience (Ogrizek et al, 2021;Paynter et al, 2018). Based on these findings and the meager amount of research specifically focused on these mothers' experience of incarceration, we have chosen to explore how the carceral environment, might affect the natural transformation of their identity that women undergo, from their child's conception to its early months of life.…”
Section: Introductionmentioning
confidence: 99%